The effect of perceived advertising effort on brand perception: implication for retailers in Hong Kong. Issue 1 (1st January 2017) - Chan, Fong Yee (Fanny); Chan, Hung Fai (Sunny); Tang, Felix
Abstract: This paper examines how advertising effort, specifically advertising creativity and advertising believability, may influence consumers' perceptions of a retailer's business philosophy, and in turn consumers' behavior toward retailers in Hong Kong. Altogether five hundred and eighty-three respondents (i.e. 320 college students and 263 shoppers) were surveyed. The results suggested that retailers that are regarded as having more creative advertising are perceived as being more learning-oriented, which leads to higher brand recognition. Meanwhile, retailers that are regarded as having more believable advertisements are perceived as having higher levels of integrity, and as a result are better recognized and more likely to be patronized. This research contributes to literature in retailing and marketing communication by establishing the antecedents and consequences of building a learning-oriented and trustworthy business philosophy in a cultural specific context. It also provides practical guidance for retailers who aim to increase brand recognition and purchase intentions through promotional effort.